Coordinated generation and transmission maintenance scheduling using mixed integer linear programming - Hussin, Siti Maherah (2016)
Scheduling of electrical equipment for maintenance tasks is crucial in power system planning as it would affect system operating cost and security. Most existing Mixed Integer Linear Programming (MILP) approaches do not address the interactions between Generation Maintenance Scheduling (GMS), Transmission Maintenance Scheduling (TMS) and Security-Constrained Unit Commitment (SCUC). This research develops a MILP algorithm for the GMS, TMS and SCUC sub-problems to improve the accuracy of coordinated generation and transmission maintenance scheduling. Power flow equation which is based on sensitivity factors is modified to improve the accuracy of transmission maintenance scheduling. To reduce the complexity of the solution procedure as well as to enhance accuracy of the maintenance scheduling model, coupling constraints equations have been formulated to integrate the GMS, TMS and SCUC sub-problems. To further improve the maintenance scheduling ability, a new technique for total operating cost assessment is developed based on an hourly basis to achieve the lowest possible operating cost. Numerical case studies were evaluated on the 6-bus, IEEE 118-bus and utility systems. A comparative study is carried out between the coordinated and individual maintenance scheduling, MILP and Lagrangian Relaxation (LR) approaches, and the maintenance scheduling based on the hourly and day-to-day basis. Simulation results show that coordinated maintenance scheduling is superior to individual maintenance scheduling as it yields lower operating costs. Besides, the proposed MILP outperformed the LR with a cost reduction of up to 5% and lowered the gap tolerance by 0.13%. Moreover, cost saving of nearly 0.14% was achieved using the hourly basis in comparison to the day-to-day basis. From this research, it can be concluded that coordinated maintenance scheduling can provide optimal maintenance schedule which would benefit most of the system planners.